A brief introduction to PAs in Germany. Issue 6 (June 2022) - Heistermann, Peter; Lang, Tamika; Heilmann, Claudia; Meyer-Treschan, Tanja
ABSTRACT: The first German physician assistant (PA) program began in 2005 at Steinbeis University in Berlin. Since 2005, there has been a rapid expansion of PA education, and 22 German universities have opened or are planning to develop PA programs. In fall 2021, about 1, 100 PAs worked in Germany, mostly in the inpatient setting, with a scope of practice focused on delegation and the performance of medical and administrative activities. After completing a PA program, students are awarded a bachelor of science; programs also offer options for specialization. With no formal PA program-specific accreditation processes, the universities are responsible for ensuring the quality and content of PA courses. The profession is not regulated in Germany, and laws to guide PA education and scope of practice are necessary for the further development of the profession.